Sir Godfrey Lagden : colonial administrator - Burton, David Raymond (Rhodes University, Faculty of Humanities, Department of History, 1991)
The thesis attempts to provide a chronological analysis of Lagden's colonial career between 1877 and 1907. The youngest son of a parish priest, Lagden received limited formal education and no military training. By a fortuitous set of circumstances, he was able, as a man on the spot, to attain high ranking posts in colonial administration. As a young man, he acquired considerable experience in the Transvaal, Egypt and the Gold Coast. However, blatant disobedience led to his dismissal from Colonial service. Fortunately for Lagden, Marshal Clarke, newly appointed Resident Commissioner of Basutoland, insisted on Lagden being appointed to his staff. Except for a brief stint in Swaziland, Lagden remained in Basutoland until 1900. With Clarke, Lagden played a prominent role in the implementation of the Imperial policy of securing the support of the Koena chiefs by allowing them to retain and consolidate their power and influence. Lagden became Resident Commissioner in Basutoland when Clarke was transferred to Zululand. He continued established policies and championed the Basotho cause by opposing the opening of Basutoland to prospectors and by stressing the industrious habits of the Basotho. His tactful and energetic handling of the rinderpest crisis reduced dramatic repercussions amongst the Basotho and enabled cooperative Koena chiefs to increase their economic and political leverage. Despite his reservations over Basotho loyalty, Lagden emerged from the South African War with an enhanced reputation as the Basotho remained loyal and energetically participated in the Imperial war effort. Largely because of his Basutoland experience, Lagden was appointed the Transvaal Commissioner of Native Affairs in 1901. He was responsible for regulating African labour supplies for the mines and delineation of African locations. His failure to procure sufficient labour and his defence of African rights earned Lagden much abusive settler condemnation. As chairman of the South African Native Affairs Commission, Lagden produced an uninspiring report conditioned by the labour shortage and his personal distaste for decisive action. Nevertheless, its advocacy of political and territorial segregation influenced successive Union governments.
Keywords: Lagden, Godfrey Yeatman, Sir, 1851-1934; South Africa -- History -- 1836-1909